Предмет: Математика,
автор: happy1976
c-(a-b)=
c+(a+b)=
c-(a+b)=
-c-(-a-b)=
(a-b)+(c-d)=
(-a-b)-(c-d)=
x+(a-b)-(c-d)=
d-(a+b)-(c-d)=
раскройте скобки по правилам дам 20 балов
Ответы
Автор ответа:
1
c-(a-b)= c-a+b
c+(a+b)= c+a+b
c-(a+b)= c-a-b
-c-(-a-b)= -c+a+b
(a-b)+(c-d)= a-b+c-d
(-a-b)-(c-d)= -a-b-c+d
x+(a-b)-(c-d)= x+a-b-c+d
d-(a+b)-(c-d)= d-a-b-c+d
happy1976:
спасибки
Похожие вопросы
Предмет: Математика,
автор: PolinaOstrouhova
Предмет: Математика,
автор: HuKoTuH
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: bakhytzhanov2005